IMPLEMENTASI TEORI KEPEMIMPINAN IOWA TERHADAP KINERJA GURU DI SMA WIJAYA PUTRA - Rohmah, Azizatur; Erianti P, Nagita Dwi; Alfiatin N, Labibah; Najwa, Fitri Adelia; Putri, Aula Rahma; Mahardika Putri, Amalia Wulan; Wahyu Pamungkas, Dimas Dzakiy; Roesminingsih, Erny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of Iowa Leadership Theory on teacher performance at SMA Wijaya Putra Surabaya. The research used a qualitative method with narrative and ethnographic approaches through observations and interviews with the principal and teachers. The results showed that the principal applied a democratic leadership style characterized by open communication, participatory decision-making, and a humanistic approach. Teachers were also given motivation, appreciation, and opportunities for professional development. Routine evaluations and participatory supervision had a positive impact on improving teacher performance. This study concludes that the democratic leadership style based on Iowa Leadership Theory positively influences teacher motivation and performance while creating a conducive educational environment.